The Effect of Debt to Equity Ratio (DER) and Inventory Turnover (ITO) on Profitability in Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2020-2024 - Made Setena; Bayu Pasupati; Ida Bagus Dharmanegara (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the effect of the Debt-to-Equity Ratio (DER) and Inventory Turnover (ITO) on profitability, measured using Return on Assets (ROA), in companies in the pharmaceutical subsector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study employs a quantitative approach using secondary data in the form of companies’ annual financial reports. The sampling technique utilized purposive sampling with a sample size of 6 companies. The analysis method employed is panel data regression, accompanied by classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results indicate that, individually, DER and ITO influence ROA with varying directions of the relationship, while simultaneously, both variables significantly affect profitability. This study implies that capital structure management and inventory efficiency are critical factors in enhancing the financial performance of pharmaceutical companies.